A Prospective, Randomized, Open-Label Trial of Early versus Late Favipiravir Therapy in Hospitalized Patients with COVID-19 - Doi, Yohei; Hibino, Masaya; Hase, Ryota; Yamamoto, Michiko; Kasamatsu, Yu; Hirose, Masahiro; Mutoh, Yoshikazu; Homma, Yoshito; Terada, Masaki; Ogawa, Taku; Kashizaki, Fumihiro; Yokoyama, Toshihiko; et al. (Antimicrobial agents and chemotherapy, 2020)
Favipiravir is an oral broad-spectrum inhibitor of viral RNA-dependent RNA polymerase that is approved for treatment of influenza in Japan. We conducted a prospective, randomized, open-label, multicenter trial of favipiravir for the treatment of COVID-19 at 25 hospitals across Japan. Eligible patients were adolescents and adults admitted with COVID-19 who were asymptomatic or mildly ill and had an Eastern Cooperative Oncology Group (ECOG) performance status of 0 or 1. Patients were randomly assigned at a 1:1 ratio to early or late favipiravir therapy (in the latter case, the same regimen starting on day 6 instead of day 1). Favipiravir is an oral broad-spectrum inhibitor of viral RNA-dependent RNA polymerase that is approved for treatment of influenza in Japan. We conducted a prospective, randomized, open-label, multicenter trial of favipiravir for the treatment of COVID-19 at 25 hospitals across Japan. Eligible patients were adolescents and adults admitted with COVID-19 who were asymptomatic or mildly ill and had an Eastern Cooperative Oncology Group (ECOG) performance status of 0 or 1. Patients were randomly assigned at a 1:1 ratio to early or late favipiravir therapy (in the latter case, the same regimen starting on day 6 instead of day 1). The primary endpoint was viral clearance by day 6. The secondary endpoint was change in viral load by day 6. Exploratory endpoints included time to defervescence and resolution of symptoms. Eighty-nine patients were enrolled, of whom 69 were virologically evaluable. Viral clearance occurred within 6 days in 66.7% and 56.1% of the early and late treatment groups (adjusted hazard ratio [aHR], 1.42; 95% confidence interval [95% CI], 0.76 to 2.62). Of 30 patients who had a fever (≥37.5°C) on day 1, times to defervescence were 2.1 days and 3.2 days in the early and late treatment groups (aHR, 1.88; 95% CI, 0.81 to 4.35). During therapy, 84.1% developed transient hyperuricemia. Favipiravir did not significantly improve viral clearance as measured by reverse transcription-PCR (RT-PCR) by day 6 but was associated with numerical reduction in time to defervescence. Neither disease progression nor death occurred in any of the patients in either treatment group during the 28-day participation. (This study has been registered with the Japan Registry of Clinical Trials under number jRCTs041190120.)